Backyards Are a Way to Promote Environmental Justice and Biodiversity Conservation in Brazilian Cities - Gedeone Ferreira Lima; Jeater Waldemar Maciel Correa Santos; Ricardo Massulo Albertin; Beatriz Martínez-Miranzo; Franco L. Souza; Fabio Angeoletto (Diversity, 2023)
Brazilian cities feature quite unequal neighborhoods. Middle-class neighborhoods have better infrastructure than those inhabited by low-income families. These inequalities are not limited to social and economic scopes; they also reach the environmental one. Tree cover in these neighborhoods is often correlated to residents’ socioeconomic status. Injustice in access to trees deprives Brazilians of their ecosystem services. Furthermore, the scarcity of tree cover in the poorest neighborhoods means less support for biodiversity. Thus, backyards can be planned to form vegetation patches capable of providing urban populations with access to green areas, as well as working as wildlife habitats.